Transfer hydrogenation reactions catalyzed by diimine and salicylaldimine ruthenium complexes - Visagie, Nicole Lynn (Stellenbosch : Stellenbosch University, 2020., 2020)
Thesis (MSc)--Stellenbosch University, 2020.